PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. NEW RATNA MOTOR SEMARANG - Putra, Hutama Dhyanto; Nugraha, Hari Susanta; Widiartanto, Widiartanto (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
Business activities are required to be alert to the global economy. The Fact as a motivation for people who engage in business activities, work and be able to create more advanced economies are better able to compete with other countries. Motivation is an important subject for managers because managers work through and with others. act as the driving motivation willingness and desire to work according to measurements and the desired limits. In addition to motivation, employee performance is also influenced by the work discipline. Where discipline is a person's awareness and willingness to comply with all company regulations and social norms in force. But in fact a high motivation to work without being followed with discipline can interfere with the performance of the employee in the employee productivity. This research intended to find out the effect of motivation and discipline on the performance of employees of PT. New Ratna Motor Semarang. This research used random sampling proporsionate techniques with 63 respondents.Analysis is conducted cross tabulation analysis, correlation, multiple regression, testing the coefficient of determination and tests of significance. From the regression analysis equation Y = 2.821 + + 0,142X2 0,339X1. Where the performance variable (Y), motivation (X1), and the Discipline of Work (X2). Hypothesis testing using a significance test showed that the two independent veriabel studied was shown to significantly affect the performance dependent variable.Respondents said about performance of employee itâ€™s good and some employee having a mistake to finish the job andÂ they donâ€™t have inisiatif to solve it. The company have a solution to complete the target and finishing a job in overtime. Motivation and discipline are high enough to have effect on the performance of employees of PT. New Ratna Motor Semarang. In addition to these two factors it is worth reviewing the company concerned and the factors or other variables related and significant effect on the performance of employees such as leadership, compensation, organizational culture, work environment, and work productivity. These factors are calculated can improve the performance of employees, so that the quality and quantity of work expected of employees in accordance with the company.